A Study of Risk Factors in Young Patients of Acute Coronary Syndrome - Biswas, Prodip Kumar; Sardar, Md Hafiz; Saha, Gopal Chandra; Hossain, Mohammad Zaid; Hossain, Mohammed Shahadat; Paul, Tushit; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2020)
Aim: The study was carried out to see the risk factors of Acute Coronary Syndrome in young patients. Materials and Methods: This is a prospective study which was carried out in 60 young patients (18-40 years of age) with a diagnosis of Acute Coronary Syndrome admitted to Dhaka medical college Hospital, Dhaka. over a period of 02 years from January 2016 to January 2018. Acute Coronary Syndrome was diagnosed by clinical history, ECG evaluation and Serum Cardiac enzyme Troponin I and CK-MB estimation. Result: Most of the patients (73%) had a sedentary lifestyle and 50% had dyslipidemia. 40% patients were taking a diet rich in fats, 37% patients were diabetic, 33% were hypertensive, 37% patients consume oral tobacco, 30% were smokers, 13% were obese and 17% were alcoholics. The family history of premature coronary artery disease was present in only 13% of cases. In our study, none of the patients had consumed oral contraceptive pills. Conclusion: The most important modifiable risk factor is the sedentary lifestyle. The commonest non-modifiable risk factor is Male sex. Smoking, oral tobacco consumption, hypertension, diabetes, dyslipidemia, and diet modification are other important modifiable risk factors in young adults. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 3-6